Single‐cell transcriptomics reveals distinct cell response between acute and chronic pulmonary infection of Pseudomonas aeruginosa - Xueli Hu; Mingbo Wu; Teng Ma; Yige Zhang; Chaoyu Zou; Ruihuan Wang; Yongxin Zhang; Yuan Ren; Qianqian Li; Huan Liu; Heyue Li; Taolin Wang; et al. (MedComm, 2022)
Abstract Knowledge of the changes in the immune microenvironment during pulmonary bacterial acute and chronic infections is limited. The dissection of immune system may provide a basis for effective therapeutic strategies against bacterial infection. Here, we describe a single immune cell atlas of mouse lungs after acute and chronic Pseudomonas aeruginosa infection using single‐cell transcriptomics, multiplex immunohistochemistry, and flow cytometry. Our single‐cell transcriptomic analysis revealed large‐scale comprehensive changes in immune cell composition and high variation in cell–cell interactions after acute and chronic P. aeruginosa infection. Bacterial infection reprograms the genetic architecture of immune cell populations. We identified specific immune cell types, including Cxcl2+ B cells and interstitial macrophages, in response to acute and chronic infection, such as their proportions, distribution, and functional status. Importantly, the patterns of immune cell response are drastically different between acute and chronic infection models. The distinct molecular signatures highlight the importance of the highly dynamic cell–cell interaction process in different pathological conditions, which has not been completely revealed previously. These findings provide a comprehensive and unbiased immune cellular landscape for respiratory pathogenesis in mice, enabling further understanding of immunologic mechanisms in infection and inflammatory diseases.